2008
DOI: 10.1002/ca.20761
|View full text |Cite
|
Sign up to set email alerts
|

The normal and abnormal anatomy of the coronary arteries

Abstract: Beneficial therapeutic options are increasingly available for coronary arterial disease. To take full advantage of these options, those performing the interventions require a thorough knowledge of the normal arrangement, and likely anatomic variations, of the coronary arterial system. A comprehensive appreciation of the architecture of the coronary arterial system, therefore, is crucial to optimal cardiac care. Simple attention to potential variations in the origin and course of the major coronary arteries can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 63 publications
0
49
0
2
Order By: Relevance
“…Other anomalous coronary artery origins were similar between the 2 groups. In this regard, previous studies have reported no relationship between the anomalous coronary artery origin and CAD (7)(8)(9).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Other anomalous coronary artery origins were similar between the 2 groups. In this regard, previous studies have reported no relationship between the anomalous coronary artery origin and CAD (7)(8)(9).…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, the relationship between the potentially lethal CAAs and the development of CADs has not been fully described so far; therefore, we planned to examine the possible relationship between the frequency of CAAs determined with angiography and CADs. The frequency of CAAs is shown to range between 0.6% and 5.6% in the general population (7)(8)(9)12,(16)(17)(18)(19). In the present study, we detected CAAs in 3.32% of our study population (270 of 8120 patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of the position of the heart within the mediastinum is essential for appropriate analysis of imaging tools (Anderson & Loukas, 2009). Due to the orientation of the aorta, the origin of the coronary arteries is not well visualised simultaneously on the same axial image.…”
Section: Normal Anatomymentioning
confidence: 99%
“…Another major pitfall in this field is the confused anatomical interpretation of the space between the aortic and pulmonary roots. In fact, there is no muscular septum between the origins of the great vessels (Loukas et al, 2009). Therefore, the visualization of an ectopic coronary artery coursing between the subpulmonary infundibulum and the interventricular septum does not necessarily imply an intramyocardial course.…”
Section: Normal Anatomymentioning
confidence: 99%